1986
DOI: 10.1007/bf02582067
|View full text |Cite
|
Sign up to set email alerts
|

Residual B-cell function in insulin-dependent (type I) diabetics with and without retinopathy

Abstract: In order to evaluate if residual B-cell function is a protecting factor against the development of diabetic retinopathy in type I diabetics we measured C-peptide levels before and after glucagon stimulation (1 mg i.v.) in 74 type I diabetics. In all patients retinopathy was assessed by fluorescein angiography and retinal lesions were classified as: grade 0, normal; grade 1, background retinopathy; grade 2, proliferative retinopathy. We then correlated the degree of retinopathy to sex, age, duration of diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
6
0
2
Order By: Relevance
“…The relationship of endogenous insulin secretion, independent of glycemic control, to the development of proliferative diabetic retinopathy and other complications is unclear (58)(59)(60)(61)(62)(63)(64)(65). Some studies suggest a protective effect of remaining endogenous insulin secretion (58-62), whereas others do not (63)(64).…”
Section: C-peptide Statusmentioning
confidence: 96%
“…The relationship of endogenous insulin secretion, independent of glycemic control, to the development of proliferative diabetic retinopathy and other complications is unclear (58)(59)(60)(61)(62)(63)(64)(65). Some studies suggest a protective effect of remaining endogenous insulin secretion (58-62), whereas others do not (63)(64).…”
Section: C-peptide Statusmentioning
confidence: 96%
“…No subgrupo de indivíduos jovens em insulinoterapia, com provável DM1, não foi identificada nenhuma associação entre níveis de PC e a frequência ou gravidade da retinopatia diabética (27). Outros estudos também foram incapazes de demonstrar papel protetor da preservação do PC no desenvolvimento de retinopatia ou outras complicações crônicas do DM1 (28,29).…”
Section: Discussionunclassified
“…Other studies also found no influence of CP stimulated with the development of retinopathy, neuropathy and/or microalbuminuria in T1DM. However, these studies included a small number of patients, with short time for monitoring and/or few chronic complications (100)(101)(102). In the pathological study of Meier et al, the number of cells found in patients with T1DM was not associated with the disease duration, but rather with glycemic control, being higher at lower blood glucose levels (90).…”
Section: Impact Of Maintenance Of Residual Insulin Secretion and Pcmentioning
confidence: 99%